A fluorogenic molecular nanoprobe with an engineered internal environment for sensitive and selective detection of biological hydrogen sulfide. Issue 14 (3rd February 2017) - Kim, Myung; Seo, Young Hun; Kim, Youngsun; Heo, Jeongyun; Jang, Woo-Dong; Sim, Sang Jun; Kim, Sehoon
Abstract : A nanoreactor approach based on the amphiphilic molecular assembly enables microscopic imaging of cellular processes and in vitro diagnostics with blood samples through selective and sensitive detection of H2 S. Abstract : A nanoreactor approach based on the amphiphilic assembly of various molecules offers a chance to finely engineer the internal reaction medium to enable highly selective and sensitive detection of H2 S in biological media, being useful for microscopic imaging of cellular processes and in vitro diagnostics with blood samples.